Yoga Therapy and Polyvagal Theory: The Convergence of Traditional Wisdom and Contemporary Neuroscience for Self-Regulation and Resilience - Sullivan, Marlysa B.; Erb, Matt; Schmalzl, Laura; Moonaz, Steffany; Noggle Taylor, Jessica; Porges, Stephen W. (Frontiers in Human Neuroscience, 2018)
Yoga therapy is a newly emerging, self-regulating complementary and integrative healthcare practice. It is growing in its professionalization, recognition and utilization with a demonstrated commitment to setting practice standards, educational and accreditation standards, and promoting research to support its efficacy for various populations and conditions. However, heterogeneity of practice, poor reporting standards, and lack of a broadly accepted understanding of the neurophysiological mechanisms involved in yoga therapy limits the structuring of testable hypotheses and clinical applications. Current proposed frameworks of yoga-based practices focus on the integration of bottom-up neurophysiological and top-down neurocognitive mechanisms. In addition, it has been proposed that phenomenology and first person ethical inquiry can provide a lens through which yoga therapy is viewed as a process that contributes towards eudaimonic well-being in the experience of pain, illness or disability. In this paper we build on these frameworks, and propose a model of yoga therapy that converges with Polyvagal Theory (PVT). PVT links the evolution of the autonomic nervous system to the emergence of prosocial behaviors and posits that the neural platforms supporting social behavior are involved in maintaining health, growth, and restoration. This explanatory model which connects neurophysiological patterns of autonomic regulation and expression of emotional and social behavior, is increasingly utilized as a framework for understanding human behavior, stress, and illness. Specifically, we describe how PVT can be conceptualized as a neurophysiological counterpart to the yogic concept of the gunas, or qualities of nature. Similar to the neural platforms described in PVT, the gunas provide the foundation from which behavioral, emotional and physical attributes emerge. We describe how these two different yet analogous frameworks—one based in neurophysiology and the other in an ancient wisdom tradition—highlight yoga therapy’s promotion of physical, mental and social wellbeing for self-regulation and resilience. This parallel between the neural platforms of PVT and the gunas of yoga is instrumental in creating a translational framework for yoga therapy to align with its philosophical foundations. Consequently, yoga therapy can operate as a distinct practice rather than fitting into an outside model for its utilization in research and clinical contexts.